Investigation of the spatial distribution pattern of 3D microcracks in single-cracked breakage. (June 2022) - Wang, Chunlai; Liu, Yubo; Hou, Xiaolin; Elmo, Davide
Abstract: The implementation of multi-crack recognition requires a theoretical basis from single-crack failure results. This study investigates the spatial distribution pattern of microcracks in single-crack-damaged coal specimens subjected to uniaxial compression. The distribution mechanism of the induced microcracks is analysed in terms of macrocracks and stress states. Gaussian and Weibull distributions are selected to explore the spatial distribution of microcracks, and quantile–quantile plots are used to study the probability density plots. The results show that the updated data better demonstrate the distribution characteristics of the ellipsoid shape visually, and the microcracks are observed to converge near the envelope. Linear distribution features are found in the scattered points of the quantile–quantile plots. The goodness-of-fit tests indicate that both Gaussian and Weibull distributions can be assigned to describe the microcrack distribution on the new axis. The probability density distribution results show that the shape is preferred to obey Gaussian distribution, whereas Weibull distribution exhibits a greater possibility of shape variation. The study results can enhance the existing knowledge on crack spatial distribution of acoustic emission positioning results associated with rock materials. In addition, the statistical results can interpret the cracks by recognising them with a specified distribution pattern.